Synthesis and Characterisation of Transition Metal Dichalcogenides and their Heterostructures - Peters, Lisanne Martha Johanna (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
Since the first isolation of graphene in 2004 the interest in 2D materials has exponentially grown. Two-dimensional layered materials demonstrate profoundly different properties when isolated in their mono- or few layer form compared to their bulk equivalents. While graphene lacks a band gap, and is thus not applicable for many logic devices, various other 2D materials, which do have a band gap, have been discovered and isolated. An important class of layered materials is the transition metal dichalcogenides (TMDs). This extended class of materials has generated generated a lot of attention due to their electronic properties, which range from metallic to semiconducting, as well as their layer-dependent properties and strong light-matter interactions. TMDs consists of a transition metal e.g. molybdenum, tungsten or platinum, sandwiched between two chalcogen atoms; sulfur, selenium or tellurium. Many of the TMDs have band gaps in a useful optical range of 1 - 2 eV. Furthermore, it is possible to open the band gap from an indirect to direct upon thinning the material from bulk to monolayer. Along with this, TMDs have also shown other interesting properties such as strong light-matter interaction and high charge-carrier mobilities. Further optimisation of the material properties can be realised by creating heterostructures of different TMDs. Heterostructures of two dissimilar TMDs result in devices with atomically sharp and clean interfaces in which the band gap can be aligned. In this work TMDs are synthesised using a microreactor chemical vapour deposition (CVD) method in which the metal precursor is brought in close proximity to the growth substrate. This method increases the reactivity on the surface and minimises the amount of metal precursor required for the synthesis. The quality and properties of the synthesised materials in this work were intensively studied by various characterisation techniques such as Raman spectroscopy, photoluminence (PL) spectroscopy, X-ray photo-electron spectroscopy and atomic force microscopy. In the first results chapter of this thesis the chemical vapour deposition synthesis of WSe2 was optimised through parametric investigation. These parameters include metal precursors, reaction time, temperature, pressure and gas flow. The parameters influence the formation of WSe2 on the growth substrate as well as the growth mechanism, nucleation density and lateral size of the flakes. Electrical FET devices with WSe2 as channel material, made from the optimised synthesis method, demonstrated p-type charge carrier transport and reasonable mobility. Collaborative work investigated the influence of environmental effects on the properties of the WSe2 FETs and the synthesised flakes were further used to demonstrate the first vertical field emission transistor. Not only the growth parameters but also the morphology of the growth substrate influences the growth mechanism of the synthesised TMD. An in-depth study on the effects of different sapphire planes and annealing of sapphire substrates on the growth of CVD MoS2 flakes showed a wide variation in alignment, growth mechanisms, flake size and flake thickness on the different sapphire planes. The size and shape of the terraces on the sapphire planes can hinder or promote the growth of MoS2 and can result in the growth of aligned MoS2. The step height between the terraces of the surface can influence the lateral growth or promote vertical, multi layer growth. Depending on the application of the MoS2, different properties are required and a particular substrate can be selected to promote MoS2 growth with these properties. Finally a direct growth CVD growth method was developed in which a micro-reactor is used to synthesise TMD heterostructures. This growth method allows the formation of both lateral and vertical heterostructures as well as sulfide and selenide heterostructures, offering a large range of possible device architectures. Both double-step and single-step synthesis of TMD heterostructures were attempted. Double-step offers more variety in possible combinations of formed heterostructures, however the crystalline quality of the TMDs and the interface is better when using a single-step approach. On top of this, single-step synthesis allowed the formation of both lateral and vertical heterostructures offering a large range of possible device architectures. The growth of of lateral and vertical heterostructures can be controlled by the concentration of the initially grown TMD. The synthesised materials were intensively studied by Raman and PL spectroscopy, XPS and TOF-SIMS as well as various AFM modes including peak force tunneling AFM. FET Devices produced from the synthesised heterostructures show interesting properties such as photoconductivity.
APPROVED
Keywords: Transition metal dichalcogenides; Heterostructures; Chemical vapour deposition; Raman spectroscopy; Atomic Force Microscopy; 2D materials; Optical lithography